An intriguing intermediate state as a bridge between antiferroelectric and ferroelectric perovskites. Issue 7 (20th May 2020) - Liu, Hui; Zhou, Zhengyang; Qiu, Yi; Gao, Botao; Sun, Shengdong; Lin, Kun; Ding, Lei; Li, Qiang; Cao, Yili; Ren, Yang; Sun, Junliang; Xing, Xianran; et al.
Abstract : An intriguing intermediate state is revealed as a bridge between conventional antiferroelectric and ferroelectric states in PbZrO3 -based perovskites Abstract : The configuration of electric or magnetic dipoles embedded into a crystal lattice gives rise to the defining physical properties of a functional material. The prevailing antiferroelectric materials have so far been allusively assumed to be in a strict antiparallel electric polarization configuration, although they have shown huge potential applications for use in electronic devices. Herein, we have revealed for the first time the complex crystal structure of an intermediate state between the two conventional antiferroelectric (AFE) and ferroelectric (FE) states in PbZrO3 -based perovskites by employing a combination of advanced synchrotron X-ray, neutron and three-dimensional (3D) electron diffraction techniques. We found that the intermediate state displays an intriguing flexible configuration of a sinusoidal wave functional with imbalanced polarization, different to the commonly believed antiparallel and balanced polarization. Such an intermediate state was concluded to act as a bridge between the conventional AFE and FE states. Our observations offer new insight into the AFE state and its transformation into the FE state. Such an intermediate state with a unique polarization configuration is believed to be a common feature that occurs in high-performance AFE perovskite materials.